What Drives Work Addicts to Action? The Extended Model of Work Craving. Issue 4 (4th July 2019) - Wojdylo, Kamila
Abstract: The theory of work craving highlights three pathological components of work addiction: the behavioral wanting component (an obsessive-compulsive desire for work), the hedonic liking components (the reduction of negative emotions and compensation for low self-worth), and the cognitive learning component (neurotic perfectionism). In this article, I link the theory of work craving with the theory of motivation and the incentive-sensitization theory of addiction and discuss three major issues: (a) obsessive-compulsive symptoms are not sufficient to diagnose workaholism; (b) two hedonic components of work craving, namely, activity-related and purpose-related incentives, should be considered; and (c) incentive-sensitization is an additional mechanism that may be prepotent for addictive working.